Kaposi varicelliform eruption: an unusual presentation caused by varicella zoster virus in a healthy adult patient - a case report - Hassan El-Masry; Safia Essam; Hamed Gaber; Nour Shaheen; Ahmed Abdelbary; Naglaa Mohamed Sayed; Salma Samir Omar (BMC Infectious Diseases, 2024)
Abstract Background Kaposi Varicelliform Eruptions (KVE), also known as eczema herpeticum, is a rare and potentially life-threatening dermatological condition primarily attributed to herpes simplex virus (HSV) infection, with less frequent involvement of Coxsackie A16, vaccinia, Varicella Zoster, and smallpox viruses. Typically associated with pre-existing skin diseases, especially atopic dermatitis, KVE predominantly affects children but can manifest in healthy adults. Characterized by painful clusters of vesicles and sores on the skin and mucous membranes, it often masquerades as other dermatological disorders. Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used for pain relief and inflammation, though their potential role as KVE triggers remains uncertain. Case report Here, we present a case of an 18-year-old female with KVE attributed to Varicella Zoster virus (VZV) and successfully treated with oral acyclovir within a week, underscoring the significance of early recognition and intervention. KVE can manifest with systemic symptoms like fever, fatigue, and lymphadenopathy and may involve multiple organ systems, necessitating possible antibiotic use for complications. Conclusion This case underscores the importance of prompt KVE identification and consideration of antiviral therapy to enhance patient outcomes. Further research is warranted to elucidate predisposing factors for this rare condition.